Rainfall Rate from Meteorological Radar Data for Microwave Applications in Malaysia - Khamis, Nor Hisham; Din, Jafri; Abdul Rahman, Tharek (2005)
This paper present the rainfall rate obtained from the analysis of a meteorological radar data in Malaysia. Rainfall rate is an important parameter for a microwave link because it enables the attenuation due to rain to be determined. An important parameter in rain attenuation studies is the rain rate for 0.01% of the time or R0.01. Design and system engineers use this value to construct conmunications system such that the link is available for 99.99% of the time. This result is obtained by utlizing the radar data from the Malaysian Meteorological Department. Knowing the rainfall rate, rain attenuation can be calculated. This informtion is useful for microwave link applications.